An Experimental Investigation of the Effects of Diesel-Ethanol Blends on the Noise and Vibrations of a Diesel Engine - Mogal, Shyam; Kapse, Arvind; Shewale, Vinod; Shete, Pankaj (Engineering, Technology & Applied Science Research, 2023)
This study performed a noise and vibration analysis of a single-cylinder diesel engine with 5, 10, and 15% ethanol concentration in diesel fuel at 20, 40, 60, 80, and 100% load and a constant engine speed of 1500rpm. Vibrations were measured at the cylinder head in the horizontal, vertical, and axial directions. The frequency and octave spectrums were obtained using an FFT analyzer. The results revealed that the E5D95 blend had significantly less vibration and noise than the E10D90 and E15D85 blends. The vibration level was minimum at 20% load and maximum at 100% load in the vertical, horizontal, and axial directions, while the highest noise level was observed for E15D85.